2008
DOI: 10.1002/jsfa.3166
|View full text |Cite
|
Sign up to set email alerts
|

Functional biscuits with PUFA‐ω3 from Isochrysis galbana

Abstract: BACKGROUND: Sweet biscuits, a traditional and nutritious food, can be healthy and very attractive when redesigned to be prepared with the addition of a natural product, the microalgal biomass of Isochrysis galbana. This marine microalga is recognised as a rich source of polyunsaturated fatty acids (PUFAs), mainly eicosapentaenoic acid (EPA; 20:5ω3), and is a promising ingredient in the food and feed industries. The importance of PUFA-ω3 (an alternative to fish oils) in food, and the need to increase the daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 22 publications
12
64
0
2
Order By: Relevance
“…3). Similar results were reported in previous studies carried out with the incorporation of flaxseeds in chikkis (Chetana and Yella Reddy 2011) and for microalgae biomass incorporated cookies 2008). Microalgae biomass addition exceeding 2 % increased the chikkis green color which results in negative a* values (Fig.…”
Section: Color Evaluationsupporting
confidence: 90%
See 1 more Smart Citation
“…3). Similar results were reported in previous studies carried out with the incorporation of flaxseeds in chikkis (Chetana and Yella Reddy 2011) and for microalgae biomass incorporated cookies 2008). Microalgae biomass addition exceeding 2 % increased the chikkis green color which results in negative a* values (Fig.…”
Section: Color Evaluationsupporting
confidence: 90%
“…These results confirmed the importance of microalgae incorporation in traditional foods as a way to enrich the nutritional value by bioactive molecules. Gouveia et al 2008 reported almost Beneficial changes achieved by increasing polyunsaturated fatty acids in chikkis are susceptible to the oxidation. PUFAs, in particular, were easily attacked by free radicals that react with their double bonds and yield products such as short-chain aldehydes, forming objectionable off-flavor compounds (Frankel 1998).…”
Section: Texture Analysismentioning
confidence: 99%
“…However, utilization of single-cell organisms (Gouveia et al, 2008) and transgenic plants (VenegasCaleró n, Syanova, & Napier, 2010) for EPA + DHA production seems to be a promising alternative. Supplementation of the animals' diet with fish products (EPA + DHA) is more efficient than linseed products (ALA) for increasing EPA + DHA content in foods; however, organoleptic properties may be compromised in this case (Moghadasian, 2008).…”
Section: Enrichment Of Foods With Epa and Dhamentioning
confidence: 98%
“…The examples comprise spaghetti enriched by adding an integrator containing EPA and DHA in a microencapsulated form to commercial semolina (Iafelice et al, 2008) or biscuits enriched with microalgal biomass of Isochrysis galbana (Gouveia et al, 2008).…”
Section: Enrichment Of Foods With Epa and Dhamentioning
confidence: 99%
“…Sudha et al (2007) studied the influence of fibre from different cereals on the rheological characteristics of wheat flour dough and on biscuits quality, showing that fibres could be used for enriching the fibre contents of biscuits. The incorporation of vegetable fibre from different sources (Piteira et al 2006) and of Chlorella vulgaris (Gouveia et al 2007) and Isochrysis galbana microalgae biomass (Gouveia et al 2008) was tested in biscuits similar to those used in this work.…”
Section: Introductionmentioning
confidence: 99%